1603c Immunisation policies and practices in occupational health: evidence and options from the literature and the field. (24th April 2018) - Porru, S; Chiappin, M; Sfriso, N
Abstract : Introduction: Exposure to biological agents occurs in many workplaces. Immunisation is a safe, cost-effective intervention for Vaccine Preventable Diseases (VPD). Although updated, evidence-based vaccination policies are available for the general population, overall there are few consensus recommendations for working populations apart from health care workers (HCWs). Methods: To evaluate current trends and evidence-based options, we performed a literature review of main online databases from 1997 to 2017, websites of various public health organisations, and professional societies, focusing on vaccination policies and practices in occupational settings. Result: Many vaccines are available for workers exposed to certain biological agents, while others are imminent. However, systematic, representative data on occupational immunisation policies, practices and coverage are lacking. Most pertain to HCWs, Influenza and HBV and coverage is sub-optimal. Variations exist by country and region for legislation, policies, schedules, groups requiring vaccination, implementation. Relevant issues include: access to vaccines; cost-effectiveness; immunisation coverage; identification susceptible of workers at-risk; fitness for work; involvement of all stakeholders. Discussion: Immunisation is an additional preventive tool to conventional workplace interventions, very effective for biohazard containment. A specific immunisation policy and practice is a strategic priority for individual workers, different workforces and the public health system. The main Occupational Health Professionals' (OHP) responsibilities are: individual, activity and area risk assessment; evaluation and provision of cost-effective vaccines; obtaining consent (or refusal) following counselling; managing non-responders and those who refuse vaccinations; career guidance; remaining updated. Mandatory immunisation should be explored in selected circumstances. OHP, employers and workers share the responsibility to implement the WHO Global Vaccine Action Plan to expand access to immunisation to all susceptible workers and strengthen routine immunisation. Policies and services should reside in the realm of Corporate Social Responsibility and be harmonised across industries, regions and countries with the ultimate goal to control and eradicate VPD in workplaces.